Suicide prevention from a public health perspective. What makes life meaningful? The opinion of some suicidal patients - Costanza, Alessandra; Amerio, Andrea; Odone, Anna; Baertschi, Marc; Richard-Lepouriel, Hélène; Weber, Kerstin; Di Marco, Sarah; Prelati, Massimo; Aguglia, Andrea; Escelsior, Andrea; Serafini, Gianluca; Amore, Mario; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Suicide is a worldwide phenomenon, with a relevant number of victims. Moreover, repercussions of suicidality-across its entire spectrum-involve not only the individual but also survivors and communities, in a profound and lasting way. As such, suicidality represents a crucial public mental health concern, in which risk/protection factors’ study represent a key issue. However, research primarily focused on suicidality risk factors. This study, moving from Frankl’s first observations on “Meaning in Life” (MiL) as protective against suicidality, aimed to identify the main themes that suicidal patients identified as MiL carriers, or potential carriers, in their existences. Methods: Qualitative study on 144 patients admitted to the Geneva University Hospital’s emergency department for suicidal ideation (SI) and suicide attempt (SA). Results: Interpersonal/affective relationships constituted the main theme (71.53%), with emphasis on family (39.80%), children/grandchildren (36.89%). Profession/education, intellectual/non-intellectual pleasures, and transcendental dimension also emerged. Conclusions: These aspects could be considered among a public health agenda’s points for suicide prevention programs taking into account also protective factors promotion/support, including community’s mental health resources. Reconnecting to introduction’s historical part, our findings are consistent with Frankl’s observations. Even if exposed to “absurd” and reluctant to deliberate on this, he seems approach Camus conceptualization who, confronted to the necessity of predictable and conform to recognizable personal patterns transcending chaos for a sense-giving perspective, invited to imagine that a meaning, even a “non-absolute meaning”, may lie in apparent smallest things and that Sisyphus can have “the possibility to revolt by trying to be happy”.